Democratic Horizons: what value change reveals about the future of democracy. Issue 5 (4th July 2021) - Welzel, Christian
ABSTRACT: Recent accounts of democratic backsliding are negligent about the cultural foundations of autocracy-vs-democracy. To bring culture back in, I demonstrate that (1) the countries' membership in culture zones explains some 70% of the global variation in autocracy-vs-democracy and (2) that this culture-bound variation has remained astoundingly constant over time – in spite of all the trending patterns in the global distribution of regime types over the last 120 years. Furthermore, the explanatory power of culture zones over autocracy-vs-democracy roots in the cultures' differentiation on "authoritarian-vs-emancipative values." Against this backdrop, lasting regime turnovers happen as a corrective response to glacially accruing regime-culture misfits – driven by generational value shifts into a pre-dominantly emancipatory direction. Consequently, the backsliding of democracies into authoritarianism is limited to societies in which emancipative values remain under-developed. Contrary to the widely cited deconsolidation-thesis, the prevalent generational profile in people's moral orientations exhibits an almost ubiquitous ascension of emancipative values that will lend more, not less, legitimacy to democracy in the future.